Uji Aktivitas Ekstrak Bunga Brokoli (Brassica oleocera L. var italica), Wortel (Daucus carota L.) dan Cabai Merah (Capsicum annum L.) Sebagai Penghambat Kolagenase - Aisyah Fatmawaty; Angriani Angriani (Jurnal Farmasi dan Ilmu Pengobatan, 2018)
Collagenase is an enzyme family of Matrix Metalloproteinase (MMP) that breaks down collagen and degrade the extracellular matrix resulting in wrinkles and changes in skin thickness. This study was aimed to determine the value of inhibition concentration of flower extracts of broccoli (Brassica oleocera L. var Italica), carrot extract (Daucus Carota L.) and extract of chili pepper (Capsicum annuum L.) as collagenase inhibitor. Collagenase inhibitory activity was determined by measuring the product resulted from the reaction of enzyme and substrate using a microplate reader at λ 345 nm. Results showed that the inhibition of the flowers of broccoli, carrot and chili pepper ekstrak were 88.49%; 53.96% and 89.21% at a concentration of 250 ug / ml.